Echocardiographic Findings Among Virally Suppressed HIV-Infected Aging Asians Compared with HIV-Negative Individuals. (1st November 2020) - Chattranukulchai, Pairoj; Thimaporn, Weerayut; Siwamogsatham, Sarawut; Satitthunmmanid, Sudarat; Sitticharoenchai, Patita; Apornpong, Tanakorn; Sangarlangkarn, Aroonsiri; Kerr, Stephen J.; Ruxrungtham, Kiat; Boonyaratavej, Smonporn; Avihingsanon, Anchalee
Abstract : Objectives: Prevalence of cardiovascular disease increases with age. Little is known about the prevalence and risk factors for echocardiographic abnormalities among older people living with HIV (PLHIV) from Asia. Design: A cross-sectional study was conducted among PLHIV aged >50 years (N = 298) on antiretroviral treatment (ART) and HIV-negative controls (N = 100) frequency matched by sex and age in Thailand. Methods: All participants underwent standard 2-dimensional transthoracic echocardiography performed by trained cardiologists who were blinded to the participant's care and HIV status. Logistic regression was used to examine the association between cardiac abnormalities and risk factors. Results: The median age was 54.7 years (60.8% men) with 37.2% having hypertension and 16.6% having diabetes mellitus. PLHIV was on ART for a median of 16.2 years with current CD4 cell counts of 616 cells per cubic millimeter. Echocardiogram abnormalities did not differ among PLHIV (55%) and the controls (60%). The major abnormalities in PLHIV were following: left ventricular (LV) hypertrophy: 37% men and 42.2% women, LV systolic dysfunction (0.7%), diastolic dysfunction (24.2%), and pulmonary hypertension (3.9%). From the multivariate analyses in PLHIV, being aged >60 years was independently associated with diastolic dysfunction, whereas female sex and left atrial volume index of >34 mL/m 2 were associated with pulmonary hypertension ( P < 0.05). None of the ART was significantly associated with any major echocardiographic abnormalities. Conclusions: In this long-term, well-suppressed, older, Asian PLHIV cohort, the prevalence of asymptomatic LV systolic dysfunction and pulmonary hypertension were relatively low, whereas the diastolic dysfunction and LV hypertrophy were common. Echocardiographic findings did not differ between PLHIV and HIV-uninfected controls.